Crystal structure of 2-(2-(6-methylpyridin-2-yl)naphthalen-1-yl)pyrimidine, C20H15N3 - Lou Xin-Hua (Zeitschrift für Kristallographie - New Crystal Structures, 2019)
C20H15N3, orthorhombic, Pbca (no. 61), a = 11.0487(4) Å, b = 13.5000(6) Å, c = 21.1032(10) Å, V = 3147.7(2) Å3, Z = 8, Rgt(F) = 0.0448, wRref(F2) = 0.1136, T = 293(2) K.